Pengaruh Judul Clickbait terhadap Persepsi Kredibilitas Berita Online di Kalangan Mahasiswa - Aprison, Leo Stepen; Putra, Delfan Eko (Lembaga Yasin AlSys, 2026)
The development of online media encourages the use of news headlines that attract readers’ attention, including clickbait headlines. This practice has the potential to influence readers’ perceptions of news credibility because the headline is the first element assessed before the news content is read. This study aims to analyze the effect of clickbait headlines on perceptions of online news credibility among university students. This study used a quantitative approach with an explanatory survey design. The research respondents consisted of 20 students selected through purposive sampling with the criterion of having accessed or read online news. Data were collected using a closed-ended Likert-scale questionnaire consisting of 16 statement items. The research instrument was declared valid, with validity values ranging from 0.842 to 0.960, and reliable, with a Cronbach’s Alpha value of 0.983. Data were analyzed using simple linear regression. The results show that clickbait headlines have a significant effect on perceptions of online news credibility, with a significance value of 0.000, a correlation coefficient of 0.962, and a coefficient of determination of 0.925. This finding confirms that news headlines play an important role in shaping perceptions of digital media credibility. The conclusion of this study indicates that the use of clickbait headlines needs to be managed ethically so that they remain attractive, accurate, relevant, and in accordance with the principles of digital journalism. The implications of this study provide a practical basis for online media managers in composing news headlines that can attract readers’ attention without reducing information credibility.